MORE THAN TASTE: INVESTIGATING THE MODERATING IMPACT OF CAFE ATMOSPHERE BETWEEN FOOD QUALITY AND SERVICE QUALITY THROUGH CUSTOMER SATISFACTION - Danny Philipe Bukidz; Thomas (Faculty of Economics and Business Universitas Pelita Harapan, 2025)
This research examines the impact moderating Café Atmosphere (CA)between food quality (FQ) and service quality (SQ) through customer satisfaction (CS) within the café sector. Research method using structural equation modeling (SEM) via SmartPLS. The goal is to explore both the direct impacts of these factors and the moderating effect of the store atmosphere on customer satisfaction. Data was gathered from 100 participants, and the analysis included both outer and inner model assessments to confirm the construction of validity and reliability. The findings indicate SQ (β = 0.391, t = 4.025, p < 0.001), FQ (β = 0.279, t = 2.996, p = 0.001), and CA (β = 0.161, t = 1.888, p = 0.030) all have a significant positive impact on customer satisfaction. Moderation analysis reveals that CA plays a significant role in moderating the relationship between SQ and CS (β = –0.176, t = 2.766, p = 0.003), suggesting that an enhanced environment can compensate for other factors. However, the store atmosphere's moderating effect on the link between FQ and CS is found to be not statistically significant (β = 0.077, t = 1.240, p = 0.108). The model explains 76.3% of the variance in CS (R² = 0.763), demonstrating substantial explanatory power. These results offer valuable theoretical insights into service management and practical recommendations for café businesses seeking to improve customer satisfaction through a comprehensive service approach.